Post Operative Pain Control Following Colon Resection and the Pendulum that has Swung from One Extreme to the Other - Mahmood, Ali; Yaakovian, Michael; Ahmed, Kamran; Mahmood, Aiva Mariam (British Journal of Healthcare and Medical Research, 2024)
The mitigation and limitation of narcotics following colon resection procedures has had many positive outcomes. The quicker return of bowel function has enabled many patients to be discharged from the hospital sooner. Earlier return to home not only provides the patients with a familiar environment to heal expediently, but also limits their exposure to nosocomial infections and provides a financial savings to healthcare. However, has the pendulum swung to far? Colon resection is a tremendous trauma to the patient. Even laparoscopy requires a small incision to extract the resected specimen, severing skin, muscle, fascia and peritoneum, inciting visceral and somatic pain. While the volume of narcotics has been markedly decreased, there is a role for narcotic usage in the post surgical colon resection patient. There is real pain that is incurred by the patient following a laparoscopic colon resection. Adequate control of this pain fosters an environment where the patient is willing to ambulate more, motivated to push themselves to recovery and build trust with their surgeons and caregivers. The purpose of our study was to evaluate the efficacy of pain medication, in particular the pain medication prescribed upon discharge. Our hypothesis centered around adequate and robust pain control would result in a motivated patient enabling a faster return to pre-surgical quality of life and fewer narcotic refills. Appropriate care with potent narcotics yield a more robust and faster recovery, with less refills on pain medication and a shorter path to recovery.